1970
DOI: 10.13057/biodiv/d170137
|View full text |Cite
|
Sign up to set email alerts
|

Ethno-medicinal plants used for herbal medication of jaundice by the indigenous community of Tripura, India

Abstract: Deb D, Datta BK, Debbarma J, Deb S. 2016. Ethno-medicinal plants used for herbal medication of jaundice by the indigenous community of Tripura,. The immemorial association of medicinal plants is highlighted in various utilization pattern by different indigenous community. An investigation was done for less known ethno-medicinal plants used for jaundice as well as some other ailments by the indigenous community of Tripura, Northeast India. The traditional utilization of plants for treatment of jaundice by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Silalahi et al (2015) have reported the local knowledge of medicinal plants and diversity of medicinal plants in the Kabanjahe traditional market, North Sumatra, Indonesia. Deb et al (2016) conducted research about ethnomedicinal plants used for herbal medication of jaundice by the indigenous community of Tripura, India. Noorul et al (2016) have studied health benefits and pharmacology of Persea americana Mill.…”
Section: Introductionmentioning
confidence: 99%
“…Silalahi et al (2015) have reported the local knowledge of medicinal plants and diversity of medicinal plants in the Kabanjahe traditional market, North Sumatra, Indonesia. Deb et al (2016) conducted research about ethnomedicinal plants used for herbal medication of jaundice by the indigenous community of Tripura, India. Noorul et al (2016) have studied health benefits and pharmacology of Persea americana Mill.…”
Section: Introductionmentioning
confidence: 99%
“…Kanchanpur, Gandacherra, Baramura, Twidu, Amarpur, Karbook Bramhi Tripuri, Jamatia, Halam, Santhal and nontribal community. Leaf Jaundice [49] 45…”
Section: Brahmmi Bhills Garits Kokanis Mavschis Valvis Pawrasmentioning
confidence: 99%
“…The distribution of the plant is covering at Philippines, Indochina, Siam, India and Indonesia (Java, Sumatra, Borneo, Sulawesi, Nusa Tenggara and Maluku). It has many benefits for health, all part of this plant contain useful compounds that can be used for traditional medicine (Deb, et al, 2016). The previous research showed that this plant is not toxic when consumed by human and animal even in high doses (Lawania et al, 2010).…”
Section: Introductionmentioning
confidence: 99%